Sendai virus efficiently infects cells via the asialoglycoprotein receptor and requires the presence of cleaved F0 precursor proteins for this alternative route of cell entry. - Bitzer, M (1997)
Biochemical evidence suggests that the asialoglycoprotein receptor (ASGP-R) can be used as an alternative receptor for a temperature-sensitive Sendai virus (SV) mutant. We now have investigated this possible alternative route of infection for SV wild-type (SV-wt) strain Fushimi by using a pair of cell lines which differ only with regard to ASGP-R expression. Infection studies after enzymatic destruction of conventional sialic acid-containing SV receptors (SA-R) revealed that only ASGP-R-expressing cells could be infected by SV-wt. This alternative route of cell entry could be completely blocked by incubation of cells with ASGP-R-specific antibodies prior to infection. Furthermore, cleavage of SV-F0 precursor protein into the subunits F1 and F2 was necessary to establish infection via ASGP-R, suggesting a fusion-mediated cell entry after binding of SV-wt to the ASGP-R on host cells. Interestingly, infection via ASGP-R was found to be nearly as efficient as infection via conventional sialic acid-containing SV receptors. A possible physiological role of the ASGP-R-mediated route of SV infection is discussed.